Percutaneous closure of giant aneurysmal coronary artery-to-coronary sinus fistulae with guidance from three-dimensional printed models: a case series. Issue 1 (10th January 2023) - Kanduri, Jaya; Truong, Quynh A; Shin, James; Wong, Shing-Chiu; Bergman, Geoffrey; Kim, Luke; Holzer, Ralf; Singh, Harsimran S
Abstract: Background: Coronary artery fistulae are abnormal communications of coronary arteries with systemic vasculature, pulmonary vasculature, or cardiac chambers. Use of multimodality imaging can be paramount to understanding anatomical and functional features of these complex vascular lesions, therefore optimizing success of potential curative interventions. Case summary: We present two patients with incidentally discovered giant aneurysmal coronary arteries with distal fistulous connections to the coronary sinus, which were successfully closed percutaneously with Amplatzer Septal Occluders using the assistance of three-dimensional (3D) printed heart models. Conclusion: Computed tomography–guided reconstruction with 3D multiplanar, multicolour printed models can help augment visuospatial understanding of the size, origin, course, and drainage of giant aneurysmal coronary artery-to-coronary sinus fistulae, and with manual bench testing can assist with choosing accurately sized and shaped devices for closure.